Hydrothermal Treatment of Magnesium Hydroxide Nanoparticles in the Presence of PEG6000 - Tang, Linsheng; Su, Mingyang; Yang, Jingwei; Yu, Kai (Asian Journal of Chemistry, 2011)
The effect of hydrothermal treatment on Mg(OH)2 nanoparticles in the presence of polyethylene glycol (PEG6000) was investigated in this work. The resultant product was characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD) and thermogravimetrydifferential thermal analysis (TG-DTA). The experimental results indicate that the hydrothermal treatment in presence of the nonionic surfactant, PEG6000 can effectively control particle growth and improve the crystallinity and dispersivity of the product due to the adsorption of PEG6000 on the surface of Mg(OH)2 throgh steric stabilization. Well-dispersed regular hexagonal flakes of Mg(OH)2 with a mean size of 61 nm and specific surface area (BET) of 62.1 m2/g were obtained by treating amorphous Mg(OH)2 particles in presence of 4.4 wt % PEG6000 at 180 ºC for 5 h.